Drug boxes for farmer groups - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
A senior animal health advisor from Malawi describes a government programme to train and equip ?farmer technicians? to perform basic animal health care.